Literasi Informasi dan Peran Perpustakaan dalam Meningkatkan SDM - Rodliyah, Ummi (Pustakaloka, 2012)
The advance of a state is decided by the human resources, particularly the information competence.Â  Libraries have an important role to increase this resource by improving the society literacy. Endeavor to upgrade the competence of infomation literacy would produce the strength of information competence, namely the competence to empower intensifying their daily activity. So that it can influence and accelerate society dynamics, and finally wouldÂ  bring out the advance of state.